IMPLEMENTASI 3D GAME ENGINE SEBAGAI VISUALISASI SISTEM NAVIGASI 6-DOF PADA ROKET KENDALI LAPAN [3D GAME ENGINE IMPLEMENTATION AS 6-DOF NAVIGATION SYSTEM VISUALIZATION AT GUIDED ROCKET OF LAPAN] - Wiryadinata, Romi; Munarto, Ri; Yusuf, Wildan; Kaharjito, Frandi A (Indonesian Journal of Aerospace, 2012)
Game engine, which are often used by game developers, has software framework that facilitates their work on important tasks such as graphic design or 3D and 2D graphics rendering. This research uses game engine called 3D state game engine for visualize 6-DOF navigation system. The software is developed for visualize range of motion of the object by reading and processing the streaming data from navigation sensor (accelerometers and rate-gyroscope). The test result show that developed software can visualize the motion of the objects in 3D animation. Software can accept and process the data as text file that is transmited in real-time through serial port. IMU hardware with sofware can use through the calibration process first, and be given a filter, so that the better results can be obtained.